Sexual dimorphism in the incidence of human cancers - Daoshan Zheng; Justyna Trynda; Cecilia Williams; Jeremy A. Vold; Justin H. Nguyen; Denise M. Harnois; Sanjay P. Bagaria; Sarah A. McLaughlin; Zhaoyu Li (BMC Cancer, 2019)
Abstract Background Sex differences in the incidences of cancers become a critical issue in both cancer research and the development of precision medicine. However, details in these differences have not been well reported. We provide a comprehensive analysis of sexual dimorphism in human cancers. Methods We analyzed four sets of cancer incidence data from the SEER (USA, 1975–2015), from the Cancer Registry at Mayo Clinic (1970–2015), from Sweden (1970–2015), and from the World Cancer Report in 2012. Results We found that all human cancers had statistically significant sexual dimorphism with male dominance in the United States and mostly significant in the Mayo Clinic, Sweden, and the world data, except for thyroid cancer, which is female-dominant. Conclusions Sexual dimorphism is a clear but mostly neglected phenotype for most human cancers regarding the clinical practice of cancer. We expect that our study will facilitate the mechanistic studies of sexual dimorphism in human cancers. We believe that fully addressing the mechanisms of sexual dimorphism in human cancers will greatly benefit current development of individualized precision medicine beginning from the sex-specific diagnosis, prognosis, and treatment.